No Evidence That Hormonal Contraceptives Affect Chemosensory Perception. (February 2021) - Schaefer, Martin; Iravani, Behzad; Arshamian, Artin; Lundström, Johan N.
The use of oral contraceptives (OC) in the form of a hormonal pill has been widespread for decades. Despite its popularity and long-time use, there is still much ambiguity and anecdotal reports about a range of potential side effects. Here, we addressed the potential effect of OC use on chemosensory perception. Previous research has almost exclusively focused on olfaction, but we expanded this to the trigeminal system and the sense of taste. We used Bayesian statistics to compare the olfactory, trigeminal, and taste detection abilities between a group of 34 normal cycling women and a group of 26 women using OC. Our results indicated that odor, trigeminal, and taste thresholds were not affected by the use of OC. Moreover, neither odor perception, nor taste perception was affected; all with Bayes factors consistently favoring the null hypothesis. The only exception to these results was odor identification where Bayes factors indicated inconclusive evidence. We conclude that effects of OC use on chemosensory perception are unlikely, and if present, likely are of no to little behavioral relevance.